2014
DOI: 10.5194/acp-14-751-2014
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of atmospheric H<sub>2</sub>SO<sub>4</sub> / H<sub>2</sub>O nucleation: organic oxidation products versus amines

Abstract: Abstract. Atmospheric H 2 SO 4 / H 2 O nucleation influencing effects have been studied in the flow tube IfT-LFT (Institute for Tropospheric Research -Laminar Flow Tube) at 293 ± 0.5 K and a pressure of 1 bar using synthetic air as the carrier gas. The presence of a possible background amine concentration in the order of 10 7 -10 8 molecule cm −3 throughout the experiments has to be taken into account. In a first set of investigations, ozonolysis of olefins (tetramethylethylene, 1-methyl-cyclohexene, α-pinene … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 65 publications
(87 reference statements)
5
49
0
Order By: Relevance
“…Comparison with the flow reactor DMA results of Berndt et al . [] show a factor of ~100 disparity from equation . A likely contributing factor to this difference is the loss of clusters to the wall before they are counted by the particle counter.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Comparison with the flow reactor DMA results of Berndt et al . [] show a factor of ~100 disparity from equation . A likely contributing factor to this difference is the loss of clusters to the wall before they are counted by the particle counter.…”
Section: Discussionsupporting
confidence: 91%
“…As shown for pyridine by Berndt et al . [], our results for TEA show that the structure of the amine plays a role in addition to its gas‐phase basicity.…”
Section: Discussionmentioning
confidence: 99%
“…Participation of amines in nucleation was studied in the laboratory for the amine-sulfuric acid-water system (e.g., Berndt et al, 2010;Erupe et al, 2011;Zollner et al, 2012;Almeida et al, 2013;Berndt et al, 2014;Kürten et al, 2014;Bianchi et al, 2014;Jen et al, 2015;Glasoe et al, 2015). Almeida et al (2013) showed for dimethylamine (DMA, (CH 3 ) 2 NH) that the presence of a few pptv enhances the aerosol formation rates of sulfuric acid by several orders of magnitude, and formation rates that are typical for atmospheric nucleation events are observed.…”
Section: Introductionmentioning
confidence: 99%
“…Other important aerosol precursors identified in several laboratory studies include ammonia and amines (Almeida et al, 2013;Ball et al, 1999;Murphy et al, 2007). Laboratory measurements (Almeida et al, 2013;Berndt et al, 2010Berndt et al, , 2014bJen et al, 2014;Kirkby et al, 2011) and computational studies (Kurtén et al, 2008;Paasonen et al, 2012) suggest that ammonia and amines can enhance particle formation but it is challenging to estimate their importance in the ambient atmosphere without comprehensive measurements of 20 their concentration in the atmosphere. Neutral sulphuric acid -amine clusters have been observed in the CLOUD chamber experiments (Kürten et al, 2014) but similar neutral clusters have not yet been detected in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%